2018
DOI: 10.1038/s41598-018-33267-4
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis bypasses epithelial barrier and modulates fibroblastic inflammatory response in an in vitro 3D spheroid model

Abstract: Porphyromonas gingivalis-induced inflammatory effects are mostly investigated in monolayer cultured cells. The aim of this study was to develop a 3D spheroid model of gingiva to take into account epithelio-fibroblastic interactions. Human gingival epithelial cells (ECs) and human oral fibroblasts (FBs) were cultured by hanging drop method to generate 3D microtissue (MT) whose structure was analyzed on histological sections and the cell-to-cell interactions were observed by scanning and transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
0
27
0
2
Order By: Relevance
“…Previous studies have reported that P. gingivalis , present in our “periodontitis-associated” biofilm model, is able to be internalised by and survive within gingival epithelial cells 3941 . Likewise, ensuing research has found that this organism is capable of bypassing the epithelial barrier in a 3D gingival epithelial and fibroblast spheroid model to induce an inflammatory response 42 . Thus, future work would benefit from assessing whether these contact-dependent mechanisms can be mimicked in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that P. gingivalis , present in our “periodontitis-associated” biofilm model, is able to be internalised by and survive within gingival epithelial cells 3941 . Likewise, ensuing research has found that this organism is capable of bypassing the epithelial barrier in a 3D gingival epithelial and fibroblast spheroid model to induce an inflammatory response 42 . Thus, future work would benefit from assessing whether these contact-dependent mechanisms can be mimicked in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Culture models made with other cell types have yielded similar results. Significant differences in the inflammatory response of cells infected with P. gingivalis (W50 and 33277 strains) were observed between 3D cultures made with collagen‐embedded fibroblasts overlaid with layers of oral ECs and 2D monolayers of oral epithelial cells (Bugueno et al, ; Pinnock, Murdoch, Moharamzadeh, Whawell, & Douglas, ). The increased secretion of proinflammatory cytokines in 3D and 2D cells treated with Aa‐LPS at the cytokine concentration associated with inflammation suggests a potential role of this antigen in the endothelial dysfunction associated with periodontopathogens (Liljestrand et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial culture. The P. gingivalis strain (ATCC 33277) was purchased from the ATCC and cultured as described previously 13 . Briefly, bacterial culture was performed under strict anaerobic conditions at 37 °C in brain-heart infusion medium (BHI) (Sigma) supplemented with hemin (5 μg/mL) and menadione (1 μg/mL).…”
Section: Methodsmentioning
confidence: 99%